Charge Storage Capability of Tunnel MnO2 and Alkaline Layered Na-MnO2 as Anode Material for Aqueous Asymmetry Supercapacitor - Radhiyah, Abd Aziz; Rajan, Jose (Elsevier, 2017)
We report here the charge storage capability of two different crystallographic structures of MnO2; tunnel and alkaline layered Na-MnO2 as a potential non-carbon based, high working potential electrode for supercapacitor applications. A hydrothermal route was used to prepare both materials. Further, XRD, FESEM, HRTEM, BET surface area analyzer and XPS techniques were used to characterize the physic-chemical property of the material. An electrochemical property of both materials was tested by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) tests in aqueous based electrolyte; alkaline and neutral. Then, the material was used to fabricate asymmetric supercapacitor (ASC) by employing the manganese based materials as an anode and commercial activated carbon (AC) as a cathode. Charge storage capabilities of both ASCs were then evaluated using CV and GCD tests. From the analysis, alkaline layered Na-MnO2//AC exhibits excellent electrochemical performance and its ASC could deliver energy density (Es) of 82 Wh/kg in 1 M of Na2SO4, which is comparable with previously obtained by manganese based ASC.